Price and Prejudice: Housing Rents Reveal Racial Animus - Marius Brülhart; Gian-Paolo Klinke; Andrea Marcucci; Dominic Rohner; Mathias Thoenig (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study market rents in the neighborhood of asylum seeker hosting centers. Our empirical setting exploits the quasi-random opening of centers and spatial allocation of asylum seekers in Switzerland. Rents within 0.7km of an active center are found on average to be 3.8% lower than rents in the control group. The price drop is more pronounced when centers host a higher share of asylum seekers from Sub-Saharan countries. In contrast, neither the religious affiliation of asylum seekers nor their inferred crime propensity affect prices significantly. Our findings are consistent with racial animus as the dominant driver of observed market outcomes.
Keywords: D90; J15; R31; 330; ethnic prejudice; willingness to pay; housing prices; refugee centers